2018
DOI: 10.1111/bjd.17034
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine, folate and vitamin B12levels in patients with psoriasis: a systematic review and meta‐analysis

Abstract: Patients with psoriasis might have higher serum homocysteine and lower folate levels than control patients without psoriasis. However, due to significant heterogeneity and other limitations, the associations require further examinations in more studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
6
20
1
Order By: Relevance
“…Very recently, a systematic review and meta-analysis demonstrated that, compared with controls, patients with psoriasis had a significantly higher serum Hcy level and a higher prevalence of HHcy [23]. Therefore, a link between HHcy and psoriasis is established.…”
Section: Hcy Levels In Patients With Psoriasismentioning
confidence: 99%
“…Very recently, a systematic review and meta-analysis demonstrated that, compared with controls, patients with psoriasis had a significantly higher serum Hcy level and a higher prevalence of HHcy [23]. Therefore, a link between HHcy and psoriasis is established.…”
Section: Hcy Levels In Patients With Psoriasismentioning
confidence: 99%
“…Even though the association between psoriasis and cardiovascular diseases is lately extensively studied, the exact underlying mechanisms have not yet been uncovered 7 . As suggested in some previously published studies, elevated serum homocysteine levels might contribute to the cardiovascular risk in psoriatic patients [8][9][10] . Homocysteine is sulfur containing amino acid, displaying atherogenic and prothrombotic features.…”
mentioning
confidence: 65%
“…A meta-analysis of 24 studies showed that psoriatic patients have higher homocysteine serum levels, a greater prevalence of hyperhomocysteinemia and, conversely, have lower serum folate levels compared to controls. Yet, the two groups did not signi cantly di er in vitamin B12 serum levels 10 . Rapid keratinocyte proliferation with high mitotic activity of basal cells, along with intestinal malabsorption caused by microscopic in ammatory changes of the intestinal mucosa, might contribute to folate de ciency in patients with psoriasis.…”
mentioning
confidence: 78%
“…Homocysteine might be involved in the pathogenesis of psoriasis [24]. Almost half of our patients suffered from hyperhomocysteinemia, which positively correlated with increasing numbers of micronucleated cells.…”
Section: Discussionmentioning
confidence: 99%